Quantifying Rate- and Temperature-Dependent Molecular Damage in Elastomer Fracture - Juliette Slootman (American Physical Society, 2020)
Elastomers are highly valued soft materials finding many applications in the engineering and biomedical fields for their ability to stretch reversibly to large deformations. Yet their maximum extensibility is limited by the occurrence of fracture, which is currently still poorly understood. Because of a lack of experimental evidence, current physical models of elastomer fracture describe the rate and temperature dependence of the fracture energy as being solely due to viscoelastic friction, with chemical bond scission at the crack tip assumed to remain constant. Here, by coupling new fluorogenic mechanochemistry with quantitative confocal microscopy mapping, we are able to quantitatively detect, with high spatial resolution and sensitivity, the scission of covalent bonds as ordinary elastomers fracture at different strain rates and temperatures. Our measurements reveal that, in simple networks, bond scission, far from being restricted to a constant level near the crack plane, can both be delocalized over up to hundreds of micrometers and increase by a factor of 100, depending on the temperature and stretch rate. These observations, permitted by the high fluorescence and stability of the mechanophore, point to an intricate coupling between strain-rate-dependent viscous dissipation and strain-dependent irreversible network scission. These findings paint an entirely novel picture of fracture in soft materials, where energy dissipated by covalent bond scission accounts for a much larger fraction of the total fracture energy than previously believed. Our results pioneer the sensitive, quantitative, and spatially resolved detection of bond scission to assess material damage in a variety of soft materials and their applications.